Heart failure in Finland: clinical characteristics, mortality, and healthcare resource use. (3rd May 2019) - Huusko, Jenni; Kurki, Samu; Toppila, Iiro; Purmonen, Timo; Lassenius, Mariann; Gullberg, Elisabet; Wirta, Sara Bruce; Ukkonen, Heikki
Abstract: Aims: The aims of this study were to describe patient characteristics of the adult chronic heart failure (HF) population and to estimate the prevalence, incidence, healthcare resource utilization (HCRU), and mortality associated with HF in Southwest Finland. Methods and results: This was a retrospective biobank and clinical registry study. Adult patients with an HF diagnosis (International Statistical Classification of Diseases and Related Health Problems (ICD) code I50) during 2004–2013 in secondary care were included in the study and compared with age‐matched and gender‐matched control patients without an I50 diagnosis. HF patients were stratified in groups by left ventricular ejection fraction (LVEF) as follows: LVEF < 40% [HF with reduced ejection fraction (HFrEF)]; LVEF ≥ 40% [HF with preserved ejection fraction (HFpEF)]; or unknown (LVEF unknown). HCRU was stratified by inpatient, outpatient, and emergency room visits. In 2013, the incidence of HF was 3.2/1000, and the prevalence was 13.9/1000 inhabitants ( n = 15 594). In the stratified analysis of HF patients ( n = 8833, average ± SD age 77.1 ± 11.2), 1115 (12.6%) patients had HFrEF (female 31.3%), 1449 (16.4%) had HFpEF (female 50.9%), and 6269 (71%) had unknown LVEF (female 52.1%). The most common co‐morbidities were essential hypertension (58%), chronic elevated serum creatinine (57.3%), atrial fibrillation and flutter (55.1%), and chronic ischaemic heart disease (46.4%). Patients with HF diagnosis had higher HCRU compared with that of age‐matched and gender‐matched controls (3.7 more days per year at the hospital for HF patients compared with the controls). The total 5 year mortality was 62.6% for HF patients and 28.3% for controls, with higher age being the strongest predictor of mortality. Moreover, multivariable Cox regression analysis showed that patients with HFrEF had a 13% (95% confidence interval 2.7–25%) increased risk of mortality compared with HFpEF patients. Conclusions: The high mortality rate and HCRU among the studied HF patients highlight the severity of the disease and the economic and social burden on both patients and society. This calls for improved methods of care for this large patient population.